Prevalence and patterns of latex glove allergy among healthcare workers in a tertiary care center in South India - A cross-sectional study - Vinupriya Sakkaravarthi; Laxmisha Chandrashekar; Medha Rajappa (Wolters Kluwer Medknow Publications, 2022)
Background: Latex glove allergy and its impact on healthcare workers (HCWs) have been studied in many countries, but the data is scarce from developing countries. Objectives: We wanted to estimate the prevalence and patterns of latex glove allergy among HCWs and to study the factors associated with it. Materials and Methods: We conducted a cross-sectional study among 1088 HCWs of a tertiary care center in South India with the screening questionnaire adopted from "Allergy and Asthma network." Skin prick test, patch test, and serum total immunoglobulin E (IgE) were performed only in consenting symptomatic HCWs. Results: The prevalence of latex glove allergy in our study subjects was 9.1% (99/1088). This includes latex protein allergy and contact dermatitis to rubber glove allergens. The most common manifestation of latex glove allergy was irritant contact dermatitis observed in 68 HCWs (68.6%). Other presentations were allergic rhinitis (40.4%), allergic contact dermatitis (17.1%), contact urticaria (11.1%), allergic conjunctivitis (6.06%), and asthma (3.03%). The risk factors associated with latex glove allergy in our study were atopy (OR = 20.51), working in both ward and operation theater (OR = 26.6), auxiliary staff (OR = 4.75), and more than ten years of hospital work experience (OR = 3.85). Conclusion: Our study reported a high prevalence of latex glove allergy. With irritant contact dermatitis being the most common manifestation in our study, HCWs at risk shall be educated on the appropriate use of gloves and hand moisturizer to prevent occupational irritant contact dermatitis (ICD). We recommend further research to address the gaps in our knowledge around latex allergy in a healthcare setting.